Characterization of West Nile Viruses Isolated from Captive American Flamingoes (Phoenicopterus ruber) in Medellin, Colombia - Osorio, Jorge E.; Ciuoderis, Karl A.; Lopera, Juan G.; Piedrahita, Leidy D.; Murphy, Darby; LeVasseur, James; Carrillo, Lina; Ocampo, Martha C.; Hofmeister, Erik (The American journal of tropical medicine and hygiene, 2012)
Serum samples from a total of 71 healthy captive birds belonging to 18 species were collected in July of 2008 in Medellin (Colombia) and tested for flaviviruses. Eighteen of 29 samples from American Flamingoes ( Phoenicopterus ruber ) were positive for West Nile virus (WNV) by reverse transcription-polymerase chain reaction. Selected positive samples were serially passaged and WNV was confirmed by immunofluorescence. Two isolates (524/08, 9835/08) were characterized in vitro and in vivo . Sequence analysis revealed WNV with 16 nucleotide substitutions resulting in six amino acid changes when compared with the NY99 strain. Colombian (COL) viruses were more closely related to Louisiana isolates from 2001. When compared with attenuated strains isolated from Texas, COL isolates differed in their plaque size and temperature sensitivity phenotype. The COL viruses were pathogenic in embryonated chicken eggs and Balb/c mice.